2014
DOI: 10.1371/journal.pone.0084786
|View full text |Cite
|
Sign up to set email alerts
|

Bmp Suppression in Mangrove Killifish Embryos Causes a Split in the Body Axis

Abstract: Bone morphogenetic proteins (Bmp) are major players in the formation of the vertebrate body plan due to their crucial role in patterning of the dorsal-ventral (DV) axis. Despite the highly conserved nature of Bmp signalling in vertebrates, the consequences of changing this pathway can be species-specific. Here, we report that Bmp plays an important role in epiboly, yolk syncytial layer (YSL) movements, and anterior-posterior (AP) axis formation in embryos of the self-fertilizing mangrove killifish, Kryptolebia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…RA inhibits the ability of the paraxial mesoderm to respond to asymmetric signalling downstream of the left-side determinant Nodal, which could cause asymmetry of somitogenesis [38]. In addition, BMP signalling has been shown to be involved in the development of the initial vertebrate body and somite [39,40] and BMP inhibitor, dorsomorphin, produces split-body phenotypes including bilaterally split somites [41]. Considering the roles of BMP and RA in somitogenesis and their demonstrated downstream effects on APOC1 protein [36], we can infer that the down-regulated expression of APOC1 protein in our study and the occurrence of CS are two concurrent phenotypes caused, at least in part, by dysregulation of some common upstream signallings such as RA and BMP.…”
Section: Discussionmentioning
confidence: 99%
“…RA inhibits the ability of the paraxial mesoderm to respond to asymmetric signalling downstream of the left-side determinant Nodal, which could cause asymmetry of somitogenesis [38]. In addition, BMP signalling has been shown to be involved in the development of the initial vertebrate body and somite [39,40] and BMP inhibitor, dorsomorphin, produces split-body phenotypes including bilaterally split somites [41]. Considering the roles of BMP and RA in somitogenesis and their demonstrated downstream effects on APOC1 protein [36], we can infer that the down-regulated expression of APOC1 protein in our study and the occurrence of CS are two concurrent phenotypes caused, at least in part, by dysregulation of some common upstream signallings such as RA and BMP.…”
Section: Discussionmentioning
confidence: 99%
“…2 E,F). sox3 was used as a marker to investigate the effect of the mutations on the neural tube ( Mourabit et al, 2014 ). stl mutants showed suppression of sox3 expression in the tail spinal cord ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If the defect caused by the noto mutation leads to failure of a fully functional tail bud formation and if that occurs before the end of epiboly, subsequent tail development may be severely affected. We have previously reported that a more severe phenotype in mangrove killifish than in zebrafish was observed in embryos treated with the Bmp inhibitor dorsomorphin ( Mourabit et al, 2014 ). Dorsomorphin-treated zebrafish embryos can complete epiboly and form a tail bud ( Yu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hybridization. in situ antisense probe for study of Mourabit et al (2014) medaka (O. latipes) ntl probe can successfully stain the Mangrove killifish (K. marmoratus) notochord by in situ hybridization. Both species are belonging to different families, however orthologous genes are highly identical and this convergence was confirmed through the test of the neighbour-joining tree, where these two species were placed in the same clade (Fig.…”
Section: Resultsmentioning
confidence: 99%